THE INFLUENCE OF COMPENSATION, MOTIVATION, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT SOHO SUHRAH BAKERY MAKASSAR - Eva Safitri (Transpublika Publisher, 2023)
Human resources play a crucial role in organizations as they directly impact employee performance and the achievement of organizational goals. Improving employee performance can be achieved through various factors such as compensation, motivation, and work discipline. This research aims to examine the individual and combined effects of compensation, work motivation, and work discipline on employee performance at Soho Suhra Bakery Makassar. The research adopts an associative quantitative method, with a population size of 30 employees. The analysis utilizes multiple linear regression techniques. The results of the T-test indicate that the compensation variable (X1), work motivation (X2), and work discipline (X3) significantly influence employee performance (Y). The t-statistic value for the compensation variable (X1) is 5.559, which is greater than the t-table value of 2.055. Conversely, the t-statistic value for work motivation (X2) is -1.461, which is less than the t-table value of 2.055, and the t-statistic value for work discipline (X3) is 0.443, also less than the t-table value of 2.055. The F-test reveals an F-statistic value of 15.303, which is greater than the F-table value of 2.99, with a significance level of 0.000. This research also demonstrates that compensation variables (X1), work motivation (X2), and work discipline (X3) influence employee performance (Y) at Soho Suhra Bakery Makassar simultaneously.